On the torsional wave dispersion in a hollow sandwich circular cylinder made from viscoelastic materials - Akbarov, S. D.; Kepceler, T. (ELSEVIER SCIENCE INC, 2015)
The dispersion of torsional wave propagation in the sandwich hollow cylinder made of linear viscoelastic materials is investigated. The investigations are carried out within the scope of the piecewise homogeneous body model by utilizing the exact field equations of viscoelasto-dynamics. The mechanical relations of the materials are described through fractional exponential operators. The analytical expression for the dispersion equation is obtained and the algorithm is developed for its numerical solution. The influence of the viscosity of the layers of the sandwich hollow cylinder is studied through the rheological parameters which characterize the characteristic creep time and long-term values of the elastic constants. It is assumed that the materials of the inner and outer cylinders are the same. Numerical results (dispersion curves) are obtained and the influence of the mentioned rheological parameters on these curves is investigated for the following two cases: attenuation of the torsional waves is dispersive (Case 1) and attenuation of the torsional waves is non dispersive (Case 2). The analytical expression is obtained for the low wave-number limit values of the torsional wave propagation velocity which is valid in Case 1. As a result of the numerical investigations, in particular, it is established that in the case where the rheological parameters of the layers are the same, the viscosity of the layers' materials causes the torsional wave propagation velocity to increase. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Attenuation; Dispersion; Sandwich hollow cylinder; Viscoelastic material; Torsional waves; PROPAGATION; Engineering; Mathematics; Mechanics